2006
DOI: 10.1016/j.ymthe.2006.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Robust systemic transduction with AAV9 vectors in mice: efficient global cardiac gene transfer superior to that of AAV8

Abstract: It has been recently shown that recombinant adeno-associated virus serotype 8 (rAAV8) is a robust alternative serotype vector that overcomes many of the limitations of rAAV2 and transduces various tissues efficiently and globally through systemic vector administration. AAV9 is a serotype newly isolated from human tissues, but our knowledge of the biology of rAAV9 in vivo is currently limited. Here, we demonstrate by a series of comprehensive side-by-side experiments with rAAV8 and 9 vectors delivered via diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
478
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 529 publications
(510 citation statements)
references
References 25 publications
31
478
2
Order By: Relevance
“…39 We observed that both, the targeted capsid selected here and the wt AAV9 capsid, mediated a comparable cardiac gene transfer upon co-injection (Figures 3b [6] and c [6]). However, while the wt AAV9 capsid enabled a wide-spread gene transfer with high levels of vg in the liver, pancreas, kidney and muscle, the peptide PSVSPRP-modified capsid provided a more specific targeting to the heart with low levels of detectable virus in other organs.…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 62%
See 3 more Smart Citations
“…39 We observed that both, the targeted capsid selected here and the wt AAV9 capsid, mediated a comparable cardiac gene transfer upon co-injection (Figures 3b [6] and c [6]). However, while the wt AAV9 capsid enabled a wide-spread gene transfer with high levels of vg in the liver, pancreas, kidney and muscle, the peptide PSVSPRP-modified capsid provided a more specific targeting to the heart with low levels of detectable virus in other organs.…”
Section: Aav Targeting Y Ying Et Almentioning
confidence: 62%
“…Although some earlier studies reported higher vg in the liver than in the heart with AAV9 vectors, 39,47,48 another publication found a better transduction of the heart than the liver of neonatal-injected animals. 45 These variations in biodistribution between different studies might be explained by different experimental conditions such as vector dose, mouse strain, gender of the mice and time point of tissue harvesting.…”
Section: Transgene Expression In Murine Hearts Following Systemic Admmentioning
confidence: 86%
See 2 more Smart Citations
“…The transduction efficiency of transgenes with viral vectors in the pancreas via intravenous administration was reported to improve under conditions of reduced blood flow to the liver, such as with a liver bypass or transient blockade of liver circulation [44,52]. However, other studies have reported that intravenous administration of AAV-8 or AAV-9 substantially delivered transgenes to the pancreas [40,53]. There is, therefore, room for debate on suitable administration routes of transgenes with viral vectors to the pancreas.…”
Section: Gene Therapy Delivery Systems For the Treatment Of Diabetes mentioning
confidence: 99%